2001
DOI: 10.1891/0886-6708.16.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Perpetrators as Victims: Understanding Violence by Female Street-Walking Prostitutes

Abstract: Little is known about the perpetration of violence by women who engage in street prostitution. While some researchers have examined the incidence of abuse among this population, the association between receipt of abuse and violence and later perpetration of violence is unclear. This study presents data from a recent evaluation of a case management program for street-walking prostitutes. A description of the program clients is provided, and factors that are associated with assaultive behavior against clients ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Still, violence against clients in prostitution may be generally underrecognized. Fifty-six percent of prostitute women participating in a case management project reported ever assaulting a client not in self-defense (44). In addition, violence perpetration against clients was modestly negatively associated with violence victimization by clients in this sample, suggesting that prostitute victims and perpetrators tend to be somewhat distinct subsets of prostitute women.…”
Section: Discussionmentioning
confidence: 74%
“…Still, violence against clients in prostitution may be generally underrecognized. Fifty-six percent of prostitute women participating in a case management project reported ever assaulting a client not in self-defense (44). In addition, violence perpetration against clients was modestly negatively associated with violence victimization by clients in this sample, suggesting that prostitute victims and perpetrators tend to be somewhat distinct subsets of prostitute women.…”
Section: Discussionmentioning
confidence: 74%
“…Each entity uses different methods and data to assess this problem which creates data mismanagement, confusion and discrepancies (Hester and Westmarland, 2004). The definition of human trafficking also remain a debatable among scholarly articles (Bales, 1999(Bales, , 2005(Bales, , 2009Arnold, Stewart and McNeece, 2001;Farley, 2009;Elkind, 2010;Kara, 2009). At international level, the Trafficking in Persons report is an attempt to collect global country level data on this issue.…”
Section: Problem Statementmentioning
confidence: 99%
“…In addition, past life events, including a negative family or childhood history, also may contribute to the risk of criminality (Arata, 2000;Arnold, Stewart, & McNeece, 2001;Chesney-Lind, 1997;L'Abate & Baggett, 1997;Nyamathi, Wenzel, Lesser, Flaskerud, & Leake, 2001;Welle et al, 1998;West, Williams, & Siegel, 2000). Depression has been associated with criminality and research has shown that criminal acts arising from a manifestation of inner tension may occur in anxiety or manic-depressive states (Cormier, 1966;De Coster, 2003;Forrest, 1977;Harrer & Kofler-Westergren, 1986).…”
Section: Introductionmentioning
confidence: 99%